The Effect of Attenuation on Simulation of Tsunami Wave Propagation Using FDM - Ahdiany, Dian; Khusnani, Azmi; Jufriansah, Adi; Prasetyo, Erwin (Journal of Novel Engineering Science and Technology, 2024)
This study seeks to investigate the shape of the surface of tsunami waves using the finite difference method and the effect of the damping function on the simulation of tsunami wave propagation using Matlab-based visualisation. The effect of attenuation on the propagation of tsunami waves is measured by the variation in energy. The results of the investigation indicate that tsunami waves have a transverse wave form, with waves propagating in a perpendicular direction. In the meantime, the analysis of the damping function reveals a decrease in the value of energy; this indicates that if the damping function is provided, it will have the effect of reducing the wave energy and propagation speed of tsunami waves. This modelling clearly and realistically illustrates the results of wave movement visualisation and provides insight for disaster mitigation and coastal protection.